2019
DOI: 10.3390/f10020185
|View full text |Cite
|
Sign up to set email alerts
|

Caribou Conservation: Restoring Trees on Seismic Lines in Alberta, Canada

Abstract: Seismic lines are narrow linear (~3–8 m wide) forest clearings that are used for petroleum exploration in Alberta’s boreal forest. Many seismic lines have experienced poor tree regeneration since initial disturbance, with most failures occurring in treed peatlands that are used by the threatened woodland caribou (Rangifer tarandus caribou). Extensive networks of seismic lines, which often reach densities of 40 km/km2, are thought to have contributed to declines in caribou. The reforestation of seismic lines is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 32 publications
1
74
0
Order By: Relevance
“…Thus, while mounding has been shown to improve tree establishment (Lieffers et al 2017;Filicetti et al 2019), we found that it resulted in a loss of bryophyte cover. Bryophyte cover, however, is only one aspect of the bryophyte community.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Thus, while mounding has been shown to improve tree establishment (Lieffers et al 2017;Filicetti et al 2019), we found that it resulted in a loss of bryophyte cover. Bryophyte cover, however, is only one aspect of the bryophyte community.…”
Section: Discussionmentioning
confidence: 72%
“…More work is needed to examine bryophyte diversity and composition between the three treatments, as well as continued monitoring to determine whether (i) bryophyte cover on the tops of the artificial hummocks will recover, (ii) tree growth is faster on these artificial hummocks, and (iii) the artificial hummocks will cause shifts in understory composition over time. Studies also need to explore differences in recovery along the bog-fen gradient (but see Filicetti et al 2019). Lastly, further research should investigate the effects of mounding on other ecological measures, especially the effects on carbon cycling and hydrological flow, as peatlands play an important role in regulating these (Rydin and Jeglum 2006;Strack et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the input CHM, output center lines, and footprint polygons, it is possible to extract a series of attributes that may be useful in classifying and assessing the conditions of linear disturbances. In the context of boreal restoration, line width, orientation, and microtopography can be important factors on the microclimate [13] and growth success of newly planted seedlings [10,66]. Therefore, the FLM attributes center lines with spatial information about their length, bearing, direction, and sinuosity.…”
Section: Line Attributionmentioning
confidence: 99%